Workshop Upscale Product “Standarisasi UMKM Sebagai Strategi Pengembangan Perekonomian Desa Janti” - Marsudi, Kenlies Era Rosalina; Muhammad Nur Hanif; Roudlotul Husna (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Janti Slahung Ponorogo Village is an area whose people are known to have many Micro, Small and Medium Enterprises (MSMEs). MSMEs in this area include catering, tailors, oyster mushroom cultivation, and also Rengginang snacks. MSMEs, the majority of whom are the older generation, have not been able to properly keep up with the development of sophisticated technology that can support the progress of their business. This has made it difficult for MSMEs in this village to develop and MSME actors claim to be overwhelmed in the face of intense competition in entrepreneurship. The main difficulty for MSMEs is that they have to understand the sophistication of technology in marketing MSME products on social media and attractive packaging. For this reason, a training and mentoring program is needed related to product branding and product packaging. The training and mentoring begins with the Upscale Product Workshop.The method used is ABCD (Asset Based Community Development) implemented through several steps namely, discovery, design, define, and reflection. The strategy used for the MSME community is in the form of invitations, explanations and direct practice. With this activity, it is hoped that people who participate in training and mentoring will have more capabilities to support their business by mastering product marketing strategies that are in line with the times and market needs that are in demand by consumers in this era and have product packaging capabilities that attract consumers' purchasing power.